A Review of the Legal Framework Governing Shipping’s Contributions to Ocean Acidification - Zaheri, Maryam (UiT Norges arktiske universitet, 2020)
This thesis is going to analyse the legal framework governing shipping’s contributions to ocean acidification and its effects on the marine environment. Meanwhile, the phenomenon of ocean acidification is emerging, the United Nation Convention on Law of the Sea (LOSC) as a main legal framework does not directly mention the acidification of the oceans by ships, the lack of legal studies in this area seems very sensible. Besides, there seems to be no specific legal framework for international cooperation against this serious environmental threat, the study intends to raise awareness of the seriousness of the phenomena and provide recommendations at the end by researching in the area. Although, it seems that much further research remains to do.